HEALTH EDUCATION ON CIGARETTE ADDICTIVE SUBSTANCE FOR ADOLESCENTS AT LKSA IHSAN SAKEENA SURAKARTA: PENDIDIKAN KESEHATAN TENTANG BAHAYA ZAT ADIKTIF ROKOK PADA REMAJA DI LKSA IHSAN SAKEENA SURAKARTA - Anis Laela Megasari; Naila Deanty Putri Ratnadhita; Widy Astuti; Tazkia Qatrunada Aulia; Rahma Nur Hidayati; Riga Alurienz; Muhammad Ridwan (Faculty of Vocational Studies, Universitas Airlangga, 2026)
Background: Smoking behavior remains a major public health problem in Indonesia. Data from the Global Youth Tobacco Survey showed that approximately 26.7% of adolescents in Indonesia had experience with smoking, while the Indonesia Health Survey 2023 reported that the highest smoking prevalence was found among adolescents aged 15–19 years, reaching 56.5%, particularly among males. Limited knowledge regarding the dangers of addictive substances in cigarettes contributes to the emergence of smoking behavior at an early age. Adolescents who are living in Child Social Welfare Institutions are also at risk due to environmental influences and limited access to health information. Objective: This activity aimed to improve participants’ knowledge at LKSA Ihsan Sakeena Surakarta regarding the dangers of cigarette addiction through health education. Method: A participatory health education approach was used, including presentations, leaflets, and interactive discussions, with evaluation through pre-test and post-test. Participants were 18 adolescents aged 8–18 years. Data were analyzed using the Wilcoxon Signed-Rank test. Results: The average knowledge score increased from 71 (pre-test) to 98.3 (post-test). Statistical analysis showed a significant difference between pre-test and post-test scores (p=0.000). Conclusion: Health education effectively improved participants’ understanding of the dangers of cigarette addiction and can serve as a preventive effort to reduce early smoking behavior.